Effects of exercise and exercise timing on energy intake and appetite control in Danish individuals with overweight or obesity with and without type 2 diabetes: a protocol for a randomised controlled cross-over trial - Louise Groth Grunnet; Martin Bæk Blond; Jonas Salling Quist; Kristine Beaulieu; Graham Finlayson; Kristine Færch; Lea Jalking; Natja Poder Launbo; Marie Møller Jensen; Hanne Enghoff Pedersen; Marina Kjærgaard Gerstenberg (BMJ Open)
Introduction The aim of this study is to investigate the effects of acute exercise on appetite control and whether this differs between morning and late afternoon in individuals with overweight/obesity with or without type 2 diabetes (T2D).Methods and analysis The hedonic and homeostatic appetite control in obesity and type 2 diabetes in the context of meal and exercise timing (TIMEX) study is a randomised, controlled, cross-over trial. Fifty-eight women and men (aged 18–75 years) with overweight or obesity (body mass index ≥25 kg/m2) with or without T2D will be recruited. All participants will complete a screening and baseline visit followed by four test visits: two morning visits and two late afternoon visits. The participants will arrive in the fasted state during the visits. During one morning visit and one late afternoon visit, the participants will engage in a 45-min bout of acute high-intensity interval exercise on an ergometer bicycle. The remaining two visits (one morning and one late afternoon visit) will include 45 min of rest. Fifteen minutes after the rest or exercise period, the participants will be presented with an ad libitum meal. Blood samples will be collected and subjective appetite will be assessed using Visual Analogue Scales in the fasted state before exercise/rest, immediately post-exercise/rest and at 15, 30, 45 and 60 min post-exercise/rest. Food reward and food preferences will be assessed using the validated diurnal version of the Steno Biometric Food Preference Task in the fasted state before exercise/rest and 15 min after the ad libitum meal (45 min post-exercise/rest). The primary outcome is the difference in ad libitum energy intake after exercise compared with rest. Secondary outcomes include eating rate; 24-hour energy intake; appetite-related metabolites and hormones, and circulating biomarkers assessed from proteomics, metabolomics and lipidomics analyses; food choice, food attention and reaction time, explicit and implicit liking and wanting for different food categories, subjective appetite; ratings of perceived exertion during exercise. All outcomes will be compared between morning and late afternoon and between participants with and without T2D.Ethics and dissemination The study has been approved by the Ethics Committee of the Capital Region of Denmark (H-22019913) and the Capital Region of Denmark’s Research Register (Privacy). The study will be conducted in accordance with the Declaration of Helsinki. All results will be published in national and international peer-reviewed journals and will be disseminated at national and international conferences.Trial registration number NCT05768958.